Current practices in physiotherapy management of COPD in Pakistan - Memon, Sajjan Iqbal; Tanveer, Fahad; Usman, Gulzar; Shakeel, Misbah (Journal of the Pakistan Medical Association, 2024)
Dear Madam, I am writing to address the usage of active cycle breathing techniques and postural drainage in the treatment of Chronic Obstructive Pulmonary Disease (COPD), with a specific emphasis on the current practices and developments in the field of pulmonary rehabilitation. COPD is a complex disease in individuals above the age of 40 with a nationwide prevalence of 2.1% 1 indicating the substantial impact of this condition that demands a multidisciplinary strategy and physiotherapy interventions including active cycle breathing techniques and postural drainage are essential in enhancing the quality of life for COPD patients in a developing country like Pakistan. Various studies have demonstrated that breathing exercises are efficacious in enhancing the strength of the muscles involved in inhalation and increasing the ability to engage in physical activity for those diagnosed with COPD.2 Physiotherapists routinely utilize the active cycle of breathing approach as a non-pharmacological method for airway clearance.3 Furthermore, the effects of oscillatory positive expiratory pressure therapy on the quality of life and objective signs of cough and sleep disturbance in COPD patients with regular sputum production have been investigated.4 The combination of postural drainage techniques and chest mobilization has been proven to effectively manage pneumonia and enhance postural alignment in patients with COPD.5 Several investigations are conducted to compare the postural alignment of COPD patients with that of healthy individuals and to establish a correlation between pulmonary function and postural alignment in the COPD group that has accounted for favorable results.6 In addition, the existing evidence suggests that active breathing strategies, such as the active cycle of breathing techniques, autogenic drainage, and forceful expiration, can be effective in managing COPD.7 At present, COPD management in Pakistan faces practical challenges such as resource limitations and training access for physiotherapists. Therefore, Cultural adaptations are needed to ensure patient acceptance and adherence. Policy support is needed to integrate physiotherapy services into healthcare systems, emphasizing long-term benefits and cost-effectiveness. Public education campaigns are crucial to raise awareness about physiotherapy interventions role in COPD management, empowering patients and families to actively participate in their care. It is crucial to acknowledge that the management of COPD necessitates a comprehensive strategy that incorporates customized physiotherapy approaches to tackle the individual difficulties encountered by patients. Physiotherapists in Pakistan have a crucial role in enhancing the results and quality of life for patients with COPD. —Continue